The weaker sex? Vulnerable men and women's resilience to socio-economic disadvantage - Mark R. Cullen; Michael Baiocchi; Karen Eggleston; Pooja Loftus; Victor Fuchs (Elsevier, 2016)
Sex differences in mortality vary over time and place as a function of social, health, and medical circumstances. The magnitude of these variations, and their response to large socioeconomic changes, suggest that biological differences cannot fully account for sex differences in survival. Drawing on a wide swath of mortality data across countries and over time, we develop a set of empiric observations with which any theory about excess male mortality and its correlates will have to contend. We show that as societies develop, M/F survival first declines and then increases, a "sex difference in mortality transition" embedded within the demographic and epidemiologic transitions. After the onset of this transition, cross-sectional variation in excess male mortality exhibits a consistent pattern of greater female resilience to mortality under socio-economic adversity. The causal mechanisms underlying these associations merit further research.